2008
DOI: 10.1159/000111641
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of β-Thalassemia in a Large Pakistani Family through Cascade Testing

Abstract: Background: We report cascade testing of a large Pakistani family for β-thalassemia alleles. The family was still practicing consanguineous marriages and was at risk of having more affected births. Objective: The objective of this study was to show that identification of disease carriers in families with index cases in order to create awareness about disease and provide genetic counseling would result in reduction of the frequency of β-thalassemia in Pakistan. Methods: In this large family with an index case, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…The frequency of consanguineous marriage in our study was much less as compared to that from a study conducted in Pakistan where cousin marriages were found to be high due to religious and cultural beliefs. [14,15] The prevalence of b-thalassemia increased with consanguineous marriage as it is an autosomal recessive disorder. A study from Iran found significant association between β-thalassemia and first cousin marriage.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of consanguineous marriage in our study was much less as compared to that from a study conducted in Pakistan where cousin marriages were found to be high due to religious and cultural beliefs. [14,15] The prevalence of b-thalassemia increased with consanguineous marriage as it is an autosomal recessive disorder. A study from Iran found significant association between β-thalassemia and first cousin marriage.…”
Section: Discussionmentioning
confidence: 99%
“…17 Cascade testing followed by genetic counseling and PND could be the method of choice to prevent affected births in a country like Pakistan. 7,8 More than 170 carrier couples have registered for PND under this program and 105 have already availed this service in a period of 2 years under this project. This pilot program resulted in about 10% reduction of b-thalassemia births in 2 years in Multan.…”
Section: Resultsmentioning
confidence: 99%
“…5,6 Cascade testing was also established at a limited scale to identify carriers in large consanguineous extended families for disease prevention. 7,8 As the carrier frequency of b-thalassemia is >5.6% in Pakistan, the number of thalassemia carriers is estimated to be 9 million and the resulting transfusion-dependent births poses a serious health burden. 9 It is estimated that 5000 to 7000 thalassemia major children are born each year in this country, whereas the total number of PND performed so far in the last 16 years are <3000.…”
mentioning
confidence: 99%
“…Cascade carrier testing is effective in other genetic disorders such as Huntington's disease, beta-thalassemia, Duchenne muscular dystrophy or fragile X syndrome [6,8,26], but it appears that the majority of at-risk family members do not have genetic testing [26]. In CF, the first experience regarding cascade carrier testing was reported in 1993 by Turner et al [12], who described the tests performed in an extended Australian family (estimated uptake rate: 21.2%).…”
Section: Discussionmentioning
confidence: 99%
“…The ultimate goal of this test is to reassure non-carrier relatives, but also to allow for early detection of couples with a 1-in-4 risk of having a CF child, who will then be able to make informed reproductive choices (such as use of prenatal diagnosis). In the absence of mutation-specific therapy for all patients, cascade carrier testing within families remains therefore a major prevention tool in the context of serious genetic diseases [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%